Branding the nation : the global business of national identity - Aronczyk, Melissa (New York Oxford University Press, 2013)
National governments around the world are turning to branding consultants, public relations advisers, and strategic communications experts to help them “brand” their jurisdiction. Using the tools, techniques, and expertise of commercial branding is believed to help nations articulate a more coherent and cohesive identity, attract foreign capital, and maintain citizen loyalty. In short, the goal of nation branding is to make the nation matter in a world where borders and boundaries appear increasingly obsolete. But what actually happens to the nation when it is reconceived as a brand? How does nation branding change the terms of politics and culture in a globalized world? Through case studies in twelve countries and in-depth interviews with nation-branding experts and their national clients, Melissa Aronczyk argues that the social, political, and cultural discourses constitutive of the nation have been harnessed in new and problematic ways, with far-reaching consequences for both our concept of the nation and our ideals of national citizenship. Branding the Nation challenges the received wisdom about the power of brands to change the world, and offers a critical perspective on these new ways of conceiving value and identity in the globalized twenty-first century.
Keywords: Identidad cultural -- Aspecto político; Marcas comerciales; Medios de comunicación social -- Aspectos políticos; Imagen corporativa; Marketing internacional; Estrategia de marketing; Relaciones internacionales; Nación